Viscous damping of gravity waves over a permeable bed - K. K. Puri (International Journal of Mathematics and Mathematical Sciences)
The damping of gravity waves over the surface of a layer of viscous fluid which overlies a porous bed saturated with the same fluid is studied. It is shown that viscosity may not be the dominant influence in the damping mechanism; the damping effects due to percolation in the fixed bed may be of the same or even higher order than those due to viscosity.